Costs and benefits of political and physical collaboration in the European Power Market - Mathias Mier; Kais Siala; Kristina Govorukha; Philip Mayer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
We use the cross-impact balance analysis to develop narratives that differ in the level of political collaboration (in terms of the stringency of the EU climate policy) and physical collaboration (possible expansion of transmission capacity between countries) in the European power market. Applying a CGE model and two power market models, we quantify the impact of the two dimensions on emission, abatement cost, and electricity prices until 2050. The most collaborative narrative leads to CO2 emissions of 90 to 139 Mt, abatement cost of 245 to 271 EUR/ton CO2, and prices of 56 to 67 EUR/MWh in 2050. The least collaborative one has emissions of 848 to 1013 Mt, cost of 378 to 559 EUR/ton, and prices of 47 to 57 EUR/MWh. In all narratives, countries at the periphery of the European market tend to experience lower prices and abate more, whereas prices are higher and abatement lower in central and Southeast Europe.
Keywords: C61; C68; Q40; Q41; 330; collaboration; energy transition; decarbonization; European power market; transmission; renewable energy; energy system modeling